Antibody response to SARS‐CoV‐2 vaccination is extremely vivacious in subjects with previous SARS‐CoV‐2 infection. Issue 7 (8th April 2021) - Callegaro, Annapaola; Borleri, Daniela; Farina, Claudio; Napolitano, Gavino; Valenti, Daniela; Rizzi, Marco; Maggiolo, Franco
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic calls for rapid actions, now principally oriented to a world‐wide vaccination campaign. In this study we verified if, in individuals with a previous SARS‐CoV‐2 infection, a single dose of messenger RNA (mRNA) vaccine would be immunologically equivalent to a full vaccine schedule in naïve individuals. Health care workers (184) with a previous SARS‐CoV‐2 infection were sampled soon before the second dose of vaccine and between 7 and 10 days after the second dose, the last sampling time was applied to SARS‐CoV‐2 naïve individuals, too. Antibodies against SARS‐CoV‐2 were measured using Elecsys Anti‐SARS‐CoV‐2 S immunoassay. The study was powered for non‐inferiority. We used non parametric tests and Pearson correlation test to perform inferential analysis. After a single vaccine injection, the median titer of specific antibodies in individuals with previous coronavirus disease 2019 was 30.527 U/ml (interquartile range [IQR]: 19.992–39.288) and in subjects with previous SARS‐CoV‐2 asymptomatic infection was 19.367.5 U/ml (IQR: 14.688–31.353) ( p = .032). Both results were far above the median titer in naïve individuals after a full vaccination schedule: 1974.5 U/ml (IQR: 895–3455) ( p < .0001). Adverse events after vaccine injection were more frequent after the second dose of vaccine (mean: 0.95; 95% confidence interval [CI]: 0.75–1.14 vs. mean: 1.91; 95% CI: 1.63–2.19) ( p < .0001) and in exposed compared to naïve (mean: 1.63; 95% CI: 1.28–1.98 vs. mean: 2.35; 95% CI: 1.87–2.82) ( p = .015). In SARS‐CoV‐2 naturally infected individuals a single mRNA vaccine dose seems sufficient to reach immunity. Modifying current dosing schedules would speed‐up vaccination campaigns. Highlights: 1) Individuals COVID 19 positive shows a single dose antibody titers 10 fold higher than naive individuals with full vaccination schedule 2) In SARS‐CoV‐2 naturally infected individuals a single mRNA vaccine dose seems sufficient to reach immunity.